Evolving concepts and management of endoleaks after endovascular aneurysm repair: where do we stand in 2019?. Issue 3 (March 2020) - Cannavale, A.; Lucatelli, P.; Corona, M.; Nardis, P.; Basilico, F.; De Rubeis, G.; Santoni, M.; Catalano, C.; Bezzi, M.
Abstract : In recent years, there has been tremendous progress in endovascular aneurysm repair (EVAR) techniques and devices. This process has seen a change in incidence, risk factors, and treatment of endoleaks as well as in follow-up protocols after EVAR. In particular, recent literature has highlighted new concepts in the evaluation and prevention/treatment of type I and II endoleak after standard EVAR. There is also recent evidence regarding new imaging protocols for follow-up after EVAR, which include magnetic resonance imaging and contrast-enhanced ultrasound. This comprehensive review aims to outline the most recent concepts on imaging follow-up, pathophysiology/risk factors, and management of endoleaks.